Co-targeting of epigenetic regulators and BCL-XL improves efficacy of immune checkpoint blockade therapy in multiple solid tumors - Yaiza Senent; Vicente Fresquet; Victoria Jiménez; Karmele Valencia; Francisco Exposito; Patxi San Martín-Úriz; Gracián Camps; Eva Fernández-Pierola; Borja Ruiz-Fernández de Córdoba; Marisol González-Huarriz; Ibon Tamayo; Ana Remírez; et al. (Molecular Cancer)
Summary Epigenetic modulators in combination with proapoptotic drugs have become the standard of care treatment in hematological malignancies. Conversely, these combinations have failed to demonstrate clinical efficacy in solid tumors. To address this discrepancy, we conducted a comprehensive analysis of the anti-tumor activity of epigenetic inhibitors in combination with BH3 mimetics that block anti-apoptotic proteins BCL-XL, BCL2 or MCL1 in a large set of solid tumor cell lines derived from patients and mouse models. Treatment with epigenetic drugs targeting DNA methyltransferase, histone methyltransferase, and histone deacetylase enzymes in combination with a BCL-XL inhibitor resulted in marked synergistic in vitro responses both in human and mouse solid tumor cell lines. This unique BCL-XL dependency was in clear contrast to hematological malignancies, which are largely dependent on BCL2 or MCL1 inhibition under epigenetic drug treatment. Mechanistically, co-targeting of epigenetic regulators and BCL-XL induced expression of endogenous retroelements that led to immunogenic cell death. We thus hypothesized that this response may sensitize tumor cells to immune checkpoint blockade (ICB). Accordingly, treatment with a triple combination of epigenetic and BCL-XL inhibitors with an anti-PD-1 monoclonal antibody in vivo reduced tumor growth and prolonged overall survival in a panel of murine syngeneic and orthotopic models of lung, colorectal and breast carcinomas, melanoma, and glioblastoma, as well as in an immunocompetent human colon cancer model. Using flow cytometry and single-cell RNA sequencing of the tumor microenvironment, we found that the broad activity of the triple therapy relied on the expansion of T and NK cells with cytotoxic potential, an increase in the M1/M2 macrophage ratio, and a reduction of immunosuppressive Treg cells, dendritic cells, and B lymphocytes. In conclusion, we report a novel regimen combining epigenetic and BCL-XL inhibitors with ICB that produces potent anti-tumor responses in multiple preclinical models of solid tumors.